2021
DOI: 10.1021/jacs.1c06461
|View full text |Cite
|
Sign up to set email alerts
|

Open Reading Frame 1 Protein of the Human Long Interspersed Nuclear Element 1 Retrotransposon Binds Multiple Equivalents of Lead

Abstract: The human long interspersed nuclear element 1 (LINE1) has been implicated in numerous diseases and has been suggested to play a significant role in genetic evolution. Open reading frame 1 protein (ORF1p) is one of the two proteins encoded in this self-replicating mobile genetic element, both of which are essential for retro­transposition. The structure of the three-stranded coiled-coil domain of ORF1p was recently solved and showed the presence of tris-cysteine layers in the interior of the coiled-coil that co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…Although it has been reported that preformed ribonucleoprotein particles (RNPs) of ORF1p and L1RNA are insensitive to up to 10 mM EDTA, exposure to mercury, arsenic, lead, nickel, aluminum, and cadmium has been shown to increase retrotransposition. , These results suggest that ORF1p is stable when bound as RNP, but that when it is unbound from RNA, metal ions interfere with the normal function, likely by increasing the stability of the homotrimer through metal coordination to the tris­(cysteine) site in the coiled coil domain. This hypothesis is supported by other structural studies that show that Hg­(II), As­(III), and Pb­(II) can bind to similar cysteine environments in 3SCCs and our previous report on lead binding to ORF1p . Of particular significance is that the oligomerization rate is critical to the ORF1p activity and we have previously shown that the oligomerization of 3SCC peptides is altered by incorporating metal binding sites and exposing them to metal ions. , Additionally, a -position (Cys) 3 sites have been shown to be preorganized for heavy metal binding, with only minor structural changes to the Cys side chains .…”
Section: Resultssupporting
confidence: 74%
See 3 more Smart Citations
“…Although it has been reported that preformed ribonucleoprotein particles (RNPs) of ORF1p and L1RNA are insensitive to up to 10 mM EDTA, exposure to mercury, arsenic, lead, nickel, aluminum, and cadmium has been shown to increase retrotransposition. , These results suggest that ORF1p is stable when bound as RNP, but that when it is unbound from RNA, metal ions interfere with the normal function, likely by increasing the stability of the homotrimer through metal coordination to the tris­(cysteine) site in the coiled coil domain. This hypothesis is supported by other structural studies that show that Hg­(II), As­(III), and Pb­(II) can bind to similar cysteine environments in 3SCCs and our previous report on lead binding to ORF1p . Of particular significance is that the oligomerization rate is critical to the ORF1p activity and we have previously shown that the oligomerization of 3SCC peptides is altered by incorporating metal binding sites and exposing them to metal ions. , Additionally, a -position (Cys) 3 sites have been shown to be preorganized for heavy metal binding, with only minor structural changes to the Cys side chains .…”
Section: Resultssupporting
confidence: 74%
“…20 We recently reported that L1ORF1p binds to lead and suggested that it could also be responsive to thiophilic metals, with important consequences on the thermodynamics and kinetics of homotrimer stability and resistance to cysteine oxidation. 21 In that previous report, we also performed a detailed structural comparison between the metal-free and Pb-bound forms of ORF1p and our de novo designed 3SCC model system. Therefore, the activity of ORF1p, and ultimately the retrotransposition properties of L1 in genomes, may be dependent on metal ion levels based on direct metal complexation.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, ORF1, characterized by three distinct domains, encodes RNA-binding protein. Even though the precise function is not fully understood, a study suggests that the strongly conserved long coiled-coil (CC) domain of the N-terminal domain contains cysteine residue layers that enable ORF1 to bind to various metal ions [ 34 , 35 , 36 ]. Both ORF1 and ORF2 proteins generally show cis preference, producing a ribonucleoprotein (RNP) particle that enables L1 to maintain its ability despite numerous non-functional elements [ 37 ].…”
Section: Non-ltr Retrotransposons In Humansmentioning
confidence: 99%